An??lise da gest??o da sustentabilidade nas empresas de software que empregam modelos de maturidade - Machado, M??rcia Cristina (2016)
This study proposes a verification of the relationship between CoBIT framework and the GRI sustainability indicators, and the identification of sustainable practices measured in technology companies that adopt CoBIT model in its management and control. In check the activities of software companies, without further analysis has perception that these are sustainable, since the production chain is electronic, distribution recently adopted is cybernetics and disposal also occurs electronically, not generating waste materials. For the study was used the methodology of study of multiple cases with the application of semi-structured interviews, analysis of documents obtained from the companies analyzed, as well as theoretical research in journals, books and CoBIT guidelines and GRI. As a result, identified a strong relationship between economic and environmental aspects proposed by the GRI indicators with the requirements of CoBIT model and a weak relationship of the social aspects of the GRI with CoBIT model. Regarding the adoption of the model CoBIT observed that companies that using the CoBIT model in its management and control, also practice and manage their sustainable actions, while promoting the dissemination of indicators through the GRI report. It was identified that even technology companies with adhere to other models of management and control, measuring their sustainable practices, do not publish their sustainability reports. The study found that organizations that do not employ models of management and control, and it does not measure its sustainable practices consequently do not publish sustainability reports. This discovery led to the development of a tool that seeks to help Brazilian software companies in the implementation of sustainable practices, and the adoption of management and control models.